Handbook of Freemasonry - Bogdan, Henrik; Snoek, Joannes A. M. (Brill handbooks on contemporary religion 1874-6691, 2014)
14 Freemasonry and Eastern Religions15 Freemasonry and Western Esotericism; 16 Freemasonry and New Religious Movements; Part 3: Ritual, Organisation, and Diffusion; 17 Masonic Rituals of Initiation; 18 Freemasonry and Performance; 19 Masonic Rites and Systems; 20 Relationships between Grand Lodges; 21 Freemasonry and Friendly Societies; Part 4: Freemasonry, Society and Politics; 22 Freemasonry and Women; 23 Freemasonry and Blacks; 24 Freemasonry and Colonialism; 25 Freemasonry and Nationalism; 26 Freemasonry and War; Part 5: Freemasonry and Culture; 27 Freemasonry and Music.